An Image Segmentation Approach Using Watershed Technique - Meher, Bimalini; Panda, Chandra Sekhar (International Journal of Computer Sciences and Engineering, 2020)
Watershed algorithm is used in image processing primarily for segmentation purposes. The main aim of this technique is to segment the image, generally when two regions of interest are close to each other i.e, their edge touch. Watersheds use many of the concepts of edge-detection, thresholding & region growing and often produce stable segmentation results. Watershed segmentation algorithm is an attractive method when compared to other segmentation algorithm. The Watershed segmentation technique can be applied to binary image, gray scale image and textural images. In many field of image processing including medical image segmentation, the watershed transform has been widely used. This method yields a result of accurate segmentation by reducing the over segmentation effect. Watershed transform is applied on distance transform, gradient image ,and marker controlled image and check which among the three yield the best result.